Attitudes towards Impression Management Tactics And its Impact on Organizational Identity Among the Managerial Employees at Al- Azhar University - Bakr, Suzan (The Arab Journal of Administration, 2018)
This study comes to investigate the impact of impression management tactics on the organizational identity using a sample from the managerial employees at Al- Azhar University, Cairo, Which total (377) employees. The study was based on descriptive analytical methodology. A questionnaire was designed to gather primary data for the study, and its validity and reliability were verified. The results Showed: there is a statistically significant correlation between impression management tactics (Ingratiation, Supplication, and Exemplification) and organizational identity. Moreover, there is a statistically significant inverse correlation was found between Intimidation and organizational identity. Lastly, there is an effect statistically significant of the impact of impression management tactics on the organizational identity excluding self-promotion. Based on these results, certain recommendations were suggested.